Balinese verbs: ‘Mapetik’ and ‘Matatah’ meaning ‘to cut’ convey ritual values - Sudipa, I Nengah; Sulasmini, Ni Made Ayu; Supartini, Ni Luh (International Journal Linguistics of Sumatra and Malay, 2025)
The aim of this writing is to discuss Balinese verbs conveying the meaning ‘to cut’ related to the sacred Hindu rites. They are referred to as the rituals of cutting hair ‘mapetik’ and tooth-filing ‘matatah’. The source of the data was from the conversations with Balinese people encountered during the ritual period. The data was collected by active participation, combined with observation and note-taking techniques. The collected data was analysed by metalanguage approach: mapping the meaning through language. Metalanguage manages to subtly map not only the meaning through entity, process, instrument(s), and the result, but    the ritual values as well. The result showed that the rites with their conveyed values rely on the meaning of the respective verbs.